Effects of different electroacupuncture/ transcutaneous electrical acupoint stimulation parameters on the pregnancy outcomes of in vitro fertilisation-embryo transfer: a systematic review and meta-analysis - Jia Liu; Jingwen Zhang; Hao Zhu; Jie Yang; Xiaoyan Zheng; Ziyu Shang; Ran Ji; Chaoliang Li; Yang Su; Ziyi Jiang; Jihang Du; Yiting Li; et al. (BMJ Open)
Background Extensive progress has been made in improving pregnancy outcomes for in vitro fertilisation and embryo transfer (IVF-ET) patients through the use of electroacupuncture (EA) and transcutaneous electrical acupoint stimulation (TEAS). However, a clear and suitable recommendation for the parameter selection scheme of EA/TEAS remains elusive.Objective To evaluate evidence-based conclusions of different EA/TEAS parameters on improvement of pregnancy outcomes in patients undergoing IVF-ET and evaluate other factors that may affect pregnancy outcomes.Method This meta-analysis systematically searched eight databases from inception to 27 August 2024, focusing on randomised controlled trials (RCTs) that evaluated the effectiveness of EA/TEAS in improving IVF-ET outcomes, with the ‌primary outcome‌ defined as ‌clinical pregnancy rate (CPR)‌, and ‌secondary outcomes‌ including ‌biochemical pregnancy rate‌ (BPR) and ‌live birth rate‌ (LBR). We further explored CPR variations associated with EA/TEAS parameters: waveform (dilatational vs continuous wave), frequency (low vs high) and treatment duration (20, 25, 30, 40, 60 min). Additionally, seven subgroup variables were analysed to identify potential influencing factors: routine treatment, intervention dose, intervention modality, mean participant age, control type, randomisation risk and allocation concealment risk.Results A total of 27 RCTs (3786 participants) were included, with the quality of evidence ranging from moderate to very low. Compared with control groups, ‌the use of dilatational waves‌ ‌significantly increased CPR‌ (RR=1.36, 95% CI [1.17 to 1.58], p<0.01, I2=0). Similarly, ‌low-frequency currents‌ ‌demonstrated a significant positive association with CPR‌ (RR=1.38, 95% CI [1.25 to 1.51], p<0.01, I2=0) and ‌a treatment duration of 30 min per session‌ ‌was associated with elevated CPR‌ (RR=1.30, 95% CI [1.19 to 1.42], p<0.01, I2=0). Subgroup analyses revealed that the effect of EA/TEAS on CPRs varied significantly depending on therapeutic dose (p=0.029), with stronger associations observed in studies involving ‌patients receiving high therapeutic dose compared with those receiving low therapeutic dose‌.Conclusion Current evidence suggests that dilatational waves, low-frequency currents and 30-minute treatment duration may improve CPRs, though findings require validation in larger trials. While parameter optimisation shows promise, stronger evidence is needed before standardising protocols. Future research should focus on rigorous RCTs to determine optimal parameters and dose-response relationships.